Perbedaan Pengetahuan Remaja Putri Tentang Perilaku Seks Pranikah Yang Diberikan Pendidikan Kesehatan Dengan Media Video Dan Lembar Balik Di Posyandu Remaja Desa Tibubeneng Tahun 2024 - Ida Ayu Putu Radnyani; Ni Komang Yuni Rahyani; Ni Made Dwi Mahayati; Ni Nyoman Suindri; Ni Wayan Suarniti; Putu Arik Herliawati (Jurnal Ners, 2025)
Risk factors for risky behavior in adolescents include a lack of knowledge about reproductive health and the impact of sexual behavior. The aim of this research is to determine differences in knowledge of young women about premarital sexual behavior who are given health education using video media and flip sheets. This type of research is pretest-posttest with control group design. Implementation in April 2024 with random sampling involving 60 teenagers divided into 2 groups. Data collection by distributing knowledge questionnaires that have been declared valid and reliable. Data analysis using univariate and bivariate. The difference between pretest and posttest knowledge scores in the video group obtained an average N-gain score of 66%, which is quite effective in increasing teenagers' knowledge. Meanwhile, the average N-gain score for the flip sheet group was 41%, which was included in the less effective category in increasing teenagers' knowledge. The results of the Mann Whitney test obtained a p-value of 0.08 (p<0.1), which means that there is a significant difference in knowledge scores and health education through video media is more effective than flip-sheet media so there is a difference in health education through video and sheet media. feedback on the knowledge of young women about premarital sexual behavior at the youth posyandu in Tibubeneng Village. It is hoped that Community Health Centers can consider video media in providing health education because it is more effective in increasing teenagers' knowledge regarding premarital sexual behavior.